Complete Blood Cell Count and Hepatokines as Inflammatory Markers in Obesity - Donma, Mustafa Metin (General Internal Medicine VI (Spring), 2024)
Obesity is a complex, multifactorial and treatable disease, which is characterized by low-grade inflammation. Pediatric obesity is a serious health problem, which may lead to obesity in adulthood. Some hematologic elements appear to be associated with inflammation. Hepatokines along with adipokines and myokines, play regulatory roles in inflammation via various pathways. They are specific and efficient mediators for the crosstalk pathways between the liver and the adipose tissue to maintain energy homeostasis. Therefore, it is plausible to relate these molecules with inflammation and obesity. So far, numerous molecules were evaluated within the scope of hepatokines. Many investigations have been performed concerning various aspects of these molecules. However, the data on their inflammatory nature and the potential associations of each with each one of complete blood cell count analysis members are scarce. The aim of this chapter was to evaluate the complicated network among weight gain, inflammation, insulin resistance, members of complete blood cell count and certain hepatokines such as α2-Heremans Schmid-Glycoprotein (Fetuin-A), Angiopoietin-like Protein-4, Fibroblast Growth Factor-21 and Leukocyte Cell-Derived Chemotaxin-2. Particularly the associations between inflammation-related hepatokines and red blood cells, white blood cells, platelets, the related counts and indices as well as ratios have been emphasized.